Self-Understanding and Lifeworld : Basic Traits of a Phenomenological Hermeneutics - Gander, Hans-Helmuth, 1954- (Book collections on Project MUSE., 2017)
What are the foundations of human self-understanding and the value of responsible philosophical questioning' Focusing on Heidegger's early work on facticity, historicity, and the phenomenological hermeneutics of factical-historical life, Hans-Helmuth Gander develops an idea of understanding that reflects our connection with the world and other, and thus invites deep consideration of phenomenology, hermeneutics, and deconstruction. He draws usefully on Husserl's phenomenology and provides grounds for exchange with Descartes, Dilthey, Nietzsche, Gadamer, Ricoeur, and Foucault. On the way to developing a contemporary hermeneutical philosophy, Gander clarifies the human relation to self in and through conversation with Heidegger's early hermeneutics. Questions about reading and writing then follow as these are the very actions that structure human self-understanding and world understanding.